4th Annual International Conference on Architecture and Civil Engineering (ACE 2016) 2016
DOI: 10.5176/2301-394x_ace16.39
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Distributions in Grassed Channel

Abstract: Studying the velocity distributions in grassed channel such as swale can help in proper design of eco-friendly channel against erosion. To understand the hydrodynamics of vegetated channel, previous studies make use of artificial vegetation to perform laboratory experiments, and this has been challenged by several researches. The present study employed the use of natural submerged vegetation to investigate the velocity distribution within a grassed flume. To achieve this, velocity profiles were measured using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Manning's equation was used for the computation of the channel dimension, and a free board of 20% of the normal flow depth was selected. The channel stability was checked based on the procedure recommended by Muhammad et al [56]. The mean velocity and tractive stress were first calculated.…”
Section: Hydraulic Evaluationmentioning
confidence: 99%
“…Manning's equation was used for the computation of the channel dimension, and a free board of 20% of the normal flow depth was selected. The channel stability was checked based on the procedure recommended by Muhammad et al [56]. The mean velocity and tractive stress were first calculated.…”
Section: Hydraulic Evaluationmentioning
confidence: 99%
“…It was found that the maximum velocity appeared to occur at the free surface of the channel, and the average velocity for all the cases was coming almost 0.75 to 0.95 of the surface velocity. Muhammad et al [20] investigated the velocity distribution within a grassed flume using natural submerged vegetation. It was found that when the vegetation was submerged, the velocity profile was found to be approximately S-shaped.…”
Section: Introductionmentioning
confidence: 99%